Systematization, Description and Territory of The Middle and Rostral Cerebral Arteries in Broad-Snouted Caimans (Caiman latirostris) - Almeida, Lygia Maria de; Campos, Rui (Acta Scientiae Veterinariae, 2018)
Background : : : Information on the arterial vascularization of the broad-snouted caimans’ brain (Caiman latirostris), a specie from the Brazilian fauna, is inexistent and the literature consulted yielded only one description about the development of embryonic circulation and post-birth cerebrovascular alterations in the brain of three caymans. The objective of this study was to describe and systematize the cerebral arterial vascularization of this reptile, by providing a standard irrigation model with its major variations, in addition to determining its territorial vascular areas. Materials, Methods & Results: Thirty heads of male broad-snouted caimans (Caiman latirostris), with the neck segment, were used in the study. Additionally, two whole female and male specimens, with approximately 3 years of age and weighing between 8 to 10 Kg were also used. The animals were sacrificed according to routine slaughterhouse norms. The heads were sectioned at the third cervical vertebra level and the azygos carotid artery was cannulated. The arterial system was washed with 0.9% saline solution and filled with red-colored latex. The pieces were fixed in formaldehyde and the encephalon removed through a window made in the cranial vault, which was followed by removal of the dura mater and dissection of the arteries. The internal carotid arteries displayed an intercarotic anastomosis in the samples examined, continuing rostrally in 100% of the cases, exiting from the skull as the internal ophthalmic artery. The internal carotid arteries divided into a rostral branch and a short caudal branch at the hypophysis level, which continued naturally as the caudal cerebral artery. The rostral branch from both right and left antimeres was shown as a single branch in 86.7% and as double branch in 13.3% of the samples, and it formed the middle cerebral artery network. The rostral cerebral artery represented the terminal branch of the internal carotid artery’s rostral branch, and an osculum anastomosis between its terminal end and its contralateral homologous artery occurred, forming the rostral communicating artery and thus closing the cerebral artery circle rostrally. Discussion: To support the results of the discussion, we used information available on the encephalic vascularization of turtles, lizards, iguanas and crocodiles, due to the absence of important publications about Caiman latirostris. One single source of blood supply, solely originated from the left aortic arch, was observed in the two whole specimens. This source was called the azygos carotid artery. Such denomination was given because these species did not show a typical common carotid artery, as the ventral part of the neck, up to the mandible, was vascularized by branches from the subclavian arteries. Therefore, we named this single and unique source as the azygos carotid artery. The cerebral arterial circle was rostrally closed by an anastomosis between the terminal ends of the rostral cerebral artery. Consequently, the blood supply to the brain was made exclusively by the carotid system. The main differences of the cerebral vascularization observed in caymans were: a network formation of the middle cerebral artery.